فعالية برنامج تدريبي قائم على الدعامات فوق المعرفية في تنمية مهارة اتخاذ القرار الجماعي المشترك في بيئة التعلم التشاركي لدى طلاب كلية التربية - عثمان، أحمد عبدالرحمن إبراهيم; شراب، نبيلة عبدالرؤوف عبدالله; خليفة، جهاد وجيه محمد رضا (جامعة العريش - كلية التربية, 2022)
هدف البحث إلى التحقق من فعالية البرنامج التدريبي القائم على الدعامات فوق المعرفية في تنمية مهارة اتخاذ القرار الجماعي المشترك في بيئة التعلم التشاركي لدى طلاب كلية التربية، تكونت عينة الدراسة التجريبية من (٦٠) طالبا وطالبة امتدت أعمارهم ما بين (١٩-٢١) سنة من طلاب كلية التربية بالعريش، وتكونت أدوات الدراسة من: مقياس مهارة اتخاذ القرار الجماعي المشترك، والبرنامج التدريبي وهما من (إعداد الباحثة)، وأظهرت نتائج الدراسة فعالية البرنامج التدريبي القائم على الدعامات فوق المعرفية في تنمية مهارة اتخاذ القرار الجماعي المشترك في بيئة التعلم التشاركي لدى طلاب كلية التربية، واستمرار فاعليته بعد الانتهاء من تطبيق البرنامج التدريبي بأربع أشهر. The current research aimed to check the effectiveness of the used program based on Metacognitive Scaffolds on Developing Collaborative Decision-making Skill in Collaborative learning environment among Faculty of Education Students, the experimental study sample consists of (60) students (boys and girls), ages between (19- 21) years. The tools used were: The scale of Collaborative learning Skills (Collaborative Decision-making Skill) prepared by the researcher, and the used training program. The results revealed the effectiveness of the used program in developing the Collaborative Decision-making Skill in collaborative learning among faculty of education students, as there were statistically significant differences between marks average of both the experimental and controlled group in the post- test of collaborative learning skills favoring the experimental group in collaborative decision- making skill, and its continued effectiveness after the completion of the application of the training program for a four months.
Keywords: الدعامات التعليمية -- البرامج التدريبية -- التعلم التشاركي -- طلبة الجامعات